Kisah Siblings Nabi Yusuf Sebagai Basis Pendidikan Anti-Bullying dalam Konteks Kekinian - Sholihat, Khodijah Amatulloh; Nurhayati, Neneng; Solihin, Mohammad; Nuryusmansyah, Roni; Khoiriyah, Khoiriyah (Jurnal Multidisiplin Ibrahimy, 2026)
This study aims to analyze the dynamics of bullying behavior experienced by Prophet Yusuf at the hands of his siblings as recorded in Surah Yusuf, and to interpret the ethical and spiritual values embedded in the narrative through a library research approach. The data were obtained from classical and contemporary Qur’anic exegesis, developmental psychology literature, and thematic studies of the Qur’an, and were analyzed using thematic tafsir and an analysis of the social context of the family. The findings indicate that the intimidation of Prophet Yusuf stemmed from jealousy, distorted perceptions, and the moral immaturity of his siblings, which subsequently led to conspiratorial actions, social exclusion, and psychological violence. The study further highlights that Prophet Yusuf’s responses marked by patience, spiritual steadfastness, and forgiveness constitute an ethical foundation that remains relevant for strengthening character education and preventing bullying within both family settings and educational institutions. This research contributes theoretically to the study of family ethics and Qur’anic values, while also opening avenues for further empirical research to enrich understanding and application in contemporary educational contexts.